2018
DOI: 10.1136/bmjopen-2017-020825
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of asthma exacerbation based on asthma severity: a nationwide population-based observational study in South Korea

Abstract: ObjectivesAsthma exacerbation, associated with many risks factors, can reflect management failure. However, little is known about how risk factors are associated with exacerbation, according to asthma severity. We aimed to investigate differences in risk factors in patients with different asthma severity and evaluate whether risk factors differed between frequent exacerbators and patients with single exacerbation.DesignNationwide population-based observational study.SettingKorean National Sample Cohort databas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
50
1
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 38 publications
6
50
1
2
Order By: Relevance
“…A history of corticosteroid bursts also was a risk factor for future exacerbation among all severities. 26 Here we demonstrated that the indicators of asthma severity, including a history of asthma-associated hospitalization, use of SABA, and a dosage of OCS use >70 mg prednisolone during hospitalized treatment in the preceding year, were independently associated with fatal asthma. These findings indicate that asthma severity is the important determinant associated with near-fatal/fatal asthma and asthma-related mortality after discharge of an asthma admission.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…A history of corticosteroid bursts also was a risk factor for future exacerbation among all severities. 26 Here we demonstrated that the indicators of asthma severity, including a history of asthma-associated hospitalization, use of SABA, and a dosage of OCS use >70 mg prednisolone during hospitalized treatment in the preceding year, were independently associated with fatal asthma. These findings indicate that asthma severity is the important determinant associated with near-fatal/fatal asthma and asthma-related mortality after discharge of an asthma admission.…”
Section: Discussionmentioning
confidence: 67%
“…These studies showed that comorbidity, which existed in older asthma patients, may have contributed to asthma mortality. 11,26,27 Whether the aforementioned factors can be utilized to independently predict the in-hospital mortality in asthma patients who require ED visits and/or hospitalizations for asthma exacerbation has not been assessed.…”
Section: Introductionmentioning
confidence: 99%
“…1,[4][5][6][7][8][9] Recently, we identified a black, exacerbation-prone asthma subgroup from a randomized trial cohort that was best characterized by subjects with an asthma exacerbation in the prior year and lower lung function, factors also associated with exacerbations in other cohorts. [10][11][12][13] Post hoc analyses of National Heart, Lung, and Blood Institute (NHLBI)-sponsored Asthma Clinical Research Network (ACRN) and AsthmaNet clinical trial cohorts have shown that African American subjects have lower lung function, a greater proportion of uncontrolled asthma, and a greater likelihood of treatment failure compared with their white counterparts. 14,15 Race and ethnic designations do not sufficiently capture the ancestral genetic, cultural, geographic, or socioeconomic contexts that underlie differences in asthma severity between racial groups.…”
mentioning
confidence: 99%
“…6 Kang HR et al, also observed similar finding that exacerbations of bronchial asthma episodes were significantly more among those aged more than 45 years. 7 Smith K et al, also noted in their study that elderly were at more risk of exacerbations of bronchial asthma. 8 Thus, all studies confirm that advanced age is associated more attacks of exacerbations of bronchial asthma.…”
Section: Discussionmentioning
confidence: 81%
“…9 But again Kang HR et al, found that it was more in females. 7 Anto JM et al, stated that the risk of exacerbations of bronchial asthma was 1.97 times more in females. 11 Thus, there is no coherence between the studies as to whether gender can be a risk factor for exacerbations of bronchial asthma.…”
Section: Discussionmentioning
confidence: 99%